St. Peter's church and square in Vienna - Kleiner, Salomon, 1703-1761 (author):::Creator::::::::::::; Pfeffel, Johann Andreas, 1674-1748 (author):::Contributor:::::::::::: (Augsburg; Pfeffel; Austria)
Color engraving of St. Peter's Church in Vienna and surroundings